Analysis of BAFF gene polymorphisms in UK Graves' disease patients. (5th November 2018) - Lane, Laura C.; Allinson, Kathleen R.; Campbell, Katy; Bhatnagar, Ishita; Ingoe, Lorna; Razvi, Salman; Cheetham, Tim; Cordell, Heather J.; Pearce, Simon H.; Mitchell, Anna L.
Summary: Objective: B lymphocyte activating factor (BAFF), a member of the tumour necrosis factor superfamily, is essential for B cell activation, differentiation and survival. Elevated circulating BAFF levels have been found in patients with several autoimmune conditions, including Graves' disease. In addition, BAFF gene variants have been associated with Graves' disease in a Taiwanese cohort, and with several other autoimmune conditions in non‐Taiwanese populations. Design and methods: We performed a case‐control association study to investigate two BAFF polymorphisms ( rs9514828 and rs4000607 ) in a UK cohort of 444 patients with Graves' disease. Genotype frequencies were compared to those from 447 local controls and more than 5000 healthy controls from the Wellcome Trust case‐control consortium (WTCCC2). Results: There was a significant difference in the frequency of the AA genotype at rs4000607 between the Graves' disease cohort and both the local controls ( P = 0.045) and the WTCCC2 controls ( P = 4.56 × 10 −6 ). Furthermore, the frequency of the A allele was found to be increased in the Graves' disease group compared to WTCCC2 controls ( P = 0.02, OR 1.20 (95% CI 1.03‐1.41). No association was observed at the rs9514828 locus. Conclusion: Dysfunction of the humoral immune system is an obligatory pathophysiological component of Graves' disease, hence BAFF is an excellent functional candidate gene. We have demonstrated, for the first time, a significant association of the BAFF polymorphism rs4000607 with Graves' disease in a UK cohort. Further work to elucidate the role of BAFF in the pathogenesis of Graves' disease is now warranted.